Acupuncture for Erectile Dysfunction: A Systematic Review. (17th January 2016) - Cui, Xiaoming; Zhou, Jing; Qin, Zongshi; Liu, Zhishun
Abstract : Background . Acupuncture is increasingly used to treat patients with erectile dysfunction (ED), and our systematic review aimed to evaluate the current evidence for the efficacy and safety of acupuncture in treating ED. Methods . An electronic search was conducted in eight databases to identify randomized controlled trials (RCTs) of acupuncture for treating erectile dysfunction that were published in English and Chinese. The Cochrane Risk of Bias tool was used to assess the risk of bias. Results . Three RCTs with a total of 183 participants met the inclusion criteria. One trial showed the beneficial effects of acupuncture compared with sham acupuncture while the others did not. One trial suggested that acupuncture combined with psychological therapy was superior to psychological therapy alone. However, the overall methodological and reporting quality of the studies was low. The safety of acupuncture for ED was unclear because there were too few reports on this topic. Conclusion . The available evidence supporting that acupuncture alone improves ED was insufficient and the available studies failed to show the specific therapeutic effect of acupuncture. Future well-designed and rigorous RCTs with a large sample size are required. This trial is registered with CRD42014013575 .